2022
DOI: 10.1002/etc.5349
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Effects of Neonicotinoid Insecticides on Wild Raccoon, Procyon lotor, in Hokkaido, Japan: Urinary Concentrations and Hepatic Metabolic Capability of Neonicotinoids

Abstract: Toxicological effects of neonicotinoid insecticides (NNIs) have been reported for mammals, such as humans, rats, and mice. However, there are limited reports on their toxic effects on wild mammals. To predict NNI‐induced toxic effects on wild mammals, it is necessary to determine the exposure levels and metabolic ability of these species. We considered that raccoons could be an animal model for evaluating NNI‐induced toxicities on wildlife because they live near agricultural fields and eat crops treated with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Analysis of stomach contents revealed that raccoons in the croplands of Hokkaido were exposed to a variety of pesticides, with high concentrations of neonicotinoid insecticides like imidacloprid, acetamiprid, and clothianidin. The concentrations of neonicotinoid insecticides in the stomach contents were found to be comparable to those identified in urine samples (Shinya et al, 2022). A significant difference in pesticide concentrations was observed between raccoons that ingested corn and those that did not, underscoring the importance of corn as a substantial contributor to pesticide exposure for raccoons inhabiting croplands.…”
Section: Pesticides Detected In Raccoons From the Croplands In Hokkaidomentioning
confidence: 59%
See 4 more Smart Citations
“…Analysis of stomach contents revealed that raccoons in the croplands of Hokkaido were exposed to a variety of pesticides, with high concentrations of neonicotinoid insecticides like imidacloprid, acetamiprid, and clothianidin. The concentrations of neonicotinoid insecticides in the stomach contents were found to be comparable to those identified in urine samples (Shinya et al, 2022). A significant difference in pesticide concentrations was observed between raccoons that ingested corn and those that did not, underscoring the importance of corn as a substantial contributor to pesticide exposure for raccoons inhabiting croplands.…”
Section: Pesticides Detected In Raccoons From the Croplands In Hokkaidomentioning
confidence: 59%
“…However, no significant difference was observed in pesticide concentrations based on the sex and age of the raccoons. When pesticide detection rates in stomach contents from the present study were compared with urine samples from our previous study (Shinya et al, 2022), the following trends were consistent in both matrices: higher detection rates of the following neonicotinoid compounds than others, such as imidacloprid (41.46% in stomach contents vs. 23.37% in urine), acetamiprid (39.02% vs. 35.59%), and clothianidin (36.59% vs. 66.10%), followed by thiamethoxam (12.20% vs. 18.64%); however, both thiacloprid (0% vs. 3.39%) and nitenpyram (0% vs. 0%) were not detected in the stomach contents (Table 3). Regarding dinotefuran (2.44% vs. 20.34%), stomach contents exhibited a notably low detection rate, whereas in urine, its detection rate was comparable to that of imidacloprid (23.37%).…”
Section: Pesticide Concentrations In the Stomach Contentsmentioning
confidence: 89%
See 3 more Smart Citations